WIPO strategy on standard essential patents 2024-2026. (WIPO publication ;, 2024)
"This document sets out a 3-year strategic plan for WIPO in the field of standard essential patents (SEPs). The Strategy, based on the guiding principles of neutrality, complementarity and voluntary nature, gives an account of WIPO's current activities and sets forth the four pillars of WIPO's upcoming work to serve as a global platform for discussion, enhance transparency, be a hub of knowledge and data, and provide meaningful services in the SEP area."--